Predictors of Patient Satisfaction in Pediatric Oncology. (November 2017) - Davis, Josh; Burrows, James F.; Ben Khallouq, Bertha; Rosen, Paul
Objective: To understand key drivers of patient satisfaction in pediatric hematology/oncology.Methods: The "top-box" scores of patient satisfaction surveys from 4 pediatric hematology/oncology practices were collected from 2012 to 2014 at an integrated Children's Health Network. One item, "Likelihood of recommending practice, " was used as the surrogate for overall patient satisfaction, and all other items were correlated to this item.Results: A total of 1244 satisfaction surveys were included in this analysis. The most important predictors of overall patient satisfaction were cheerfulness of practice ( r = .69), wait time ( r = .60), and staff working together ( r = .60). The lowest scoring items were getting clinic on phone, information about delays, and wait time at clinic.Conclusion: Families bringing their children for outpatient care in a hematology/oncology practice want to experience a cheerful and collaborative medical team. Wait time at clinic may be a key driver in the overall experience for families with children with cancer. Future work should be directed at using this evidence to drive patient experience improvement processes in pediatric hematology/oncology.